Chipping in on the role of conscious processing during children's motor learning by analogy. Issue 3 (June 2019) - Duijn, Tina van; Thomas, Simon; Masters, Rich SW
The capacity for storing and manipulating information (a function of working memory) is not fully developed until adulthood, so children are not always able to process explicit instructions when learning a new skill. A teaching method that may solve this problem is analogy learning, which compares the to-be-learned skill with a well-known concept by way of a single metaphorical instruction. In adults, analogy learning has been shown to lead to lower load on working memory by reducing the need for conscious processing; however, the effects are unclear in children. If analogy instructions work similarly in children, the propensity to consciously control movements may affect how well children learn by analogy. It is in the interest of coaches and teachers to determine whether analogy instructions can be used to reduce conscious processing in children, and whether propensity for conscious control of movements (movement specific reinvestment) predicts benefits from analogy learning. Thirteen-year-old golf novices (n = 44) were pre-tested and post-tested after practicing a golf-chipping task using explicit rules. One week later, an analogy for learning the golf chip was introduced, and an identical set of post-tests was repeated. Propensity for conscious control/reinvestment predicted improvement in accuracy after the analogy was introduced. Children's motor learning by analogy may be affected by their propensity for conscious control of movements, which suggests that coaches should adapt instructions to individual differences between learners.